Response to a case report: Idiopathic hypereosinophilic syndrome in remission with benralizumab treatment after relapse with mepolizumab. Issue 2 (4th January 2021) - Requena, Gema; Roufosse, Florence; Baylis, Lee D.; Steinfeld, Jonathan
Abstract : See related Reply